Burden of osteoarthritis in older adults (aged ≥55 years) in the United States and China: a comparative analysis of temporal trends, risk factor contributions, and projected burden to 2030 using global burden of disease study 2021 data - Han, Xuequan; Zhang, Chi; Guan, Bin; Zhou, Hengxing; Kong, Xiaohong; Feng, Shiqing (Frontiers in Medicine, 2025)
ObjectiveOsteoarthritis (OA) is a leading cause of disability worldwide, with aging populations and rising obesity rates being notable contributing factors. This study examines OA burden trends from 1990 to 2021 among individuals aged 55 and older in China and the United States (US), with projections through 2030, while addressing the gap in comprehensive, site-specific, and age-stratified OA data in the US.MethodsData from the Global Burden of Disease (GBD) 2021 study were used to evaluate age-standardized rates of incidence (ASIR), prevalence (ASPR), and disability-adjusted life years (AS-DALYs), as well as absolute numbers and age-specific rates, for OA and site-specific OA. Temporal trends were analyzed using Joinpoint regression, while age-period-cohort (APC) analysis was employed to assess contributing factors. Bayesian APC modeling was applied to project OA burden trends through 2030.ResultsFrom 1990 to 2021, the OA burden exhibited distinct yet noteworthy trends in the US and China. The US consistently maintained markedly higher age-standardized incidence, prevalence, and disability rates than China, reflecting a substantial and persistent OA burden among older adults. However, China experienced a more rapid escalation in disease burden, especially for hand and hip OA. For example, the average annual percentage change (AAPC) of ASIR and ASPR in China reached 0.46%, surpassing the US (0.20 and 0.16%, respectively). Notably, hand OA prevalence in China showed an exceptionally steep rise (AAPC = 1.6%), far outpacing the US (0.2%). In absolute numbers, China bore a much larger burden due to its population size. Projections to 2030 indicate a continued global increase in OA burden, with the US expected to retain high prevalence and China projected to undergo steeper growth, highlighting differing but significant public health challenges in both countries.ConclusionThis study demonstrates a persistently high OA burden in the US, while China shows rapidly increasing rates, especially for hand and hip OA in older adults. With differing trajectories projected through 2030, region-specific strategies are warranted: China should focus on curbing accelerating incidence and addressing modifiable risks like obesity, while the US should enhance management to reduce disability in a population already facing high OA prevalence.